From birth to function: Male gametophyte development in flowering plants. (October 2021) - Huang, Jiaying; Dong, Juan; Qu, Li-Jia
Abstract: Male germline development in flowering plants involves two distinct and successive phases, microsporogenesis and microgametogenesis, which involve one meiosis followed by two rounds of mitosis. Many aspects of distinctions after mitosis between the vegetative cell and the male germ cells are seen, from morphology to structure, and the differential functions of the two cell types in the male gametophyte are differentially needed and required for double fertilization. The two sperm cells, carriers of the hereditary substances, depend on the vegetative cell/pollen tube to be delivered to the female gametophyte for double fertilization. Thus, the intercellular communication and coordinated activity within the male gametophyte probably represent the most subtle regulation in flowering plants to guarantee the success of reproduction. This review will focus on what we have known about the differentiation process and the functional diversification of the vegetative cell and the male germ cell, the most crucial cell types for plant fertility and crop production. Highlights: Plant microspores produce daughter cells with distinct cell fates through polarized mitosis. Microspore daughter cells with different cell fates show distinct intracellular epigenetic patterns. These differences mediate distinct function of the cells during fertilization.